Perception of Library Professionals regarding HRD Climate: An Empirical Study - Renu; Kadyan, Sanjiv (Journal of Information and Knowledge, 2021)
The present paper is an attempt to study the effect of gender and nature of job on perception of Human Resource Development (HRD) climate among professional library employees. The primary data was collected from professionals working in different agricultural university libraries (regular and deemed) of five northern Indian states. Descriptive survey design was adopted for this study. A sample of 96 male and female library professionals with different jobs constituted the sample for the present study. Mean, standard deviation, ‘t’ test and ANOVA were used to analyze the data. The analysis showed that gender has no impact on perception of HRD climate, both male and female were equally satisfied in the context of HRD climate while impact of nature of job was observed. Permanent employees were found more satisfied with HRD climate than respondents working part-time staff and on and ad-hoc basis. Designation of library professional also influences perception of HRD climate.